(untitled) (Clinics, 2021)
OBJECTIVES: To explore the effect of tumor and normal lung volumes on lung volume-dose parameters in patients with non-small-cell lung cancer (NSCLC) who had undergone intensity-modulated radiation therapy (IMRT). METHODS: The clinical data of 208 patients with NSCLC who underwent radical IMRT between June 2014 and June 2018 were retrospectively analyzed. A regression model curve was used to evaluate the effect of tumor and normal lung volumes on normal lung relative volumes receiving greater than 5 and 20 Gy (V5, V20), on mean lung dose (MLD), and on absolute volumes spared from greater than 5 and 20 Gy (AVS5, AVS20). RESULTS: The V5, V20, and MLD of the bilateral lung were fitted to a quadratic equation curve with the change in tumor volume, which increased initially and then decreased when the tumor volume increased. The V5, V20, and MLD of the lung reached their apex when the tumor volumes were 288.07, 341.69, and 326.83 cm3, respectively. AVS5 and AVS20 decreased in a logarithmic curve with an increase in tumor volume. The V5, V20, and MLD of the small normal lung volume group were all significantly higher than those of the large normal lung volume group (p<0.001, p=0.004, p=0.002). However, the AVS5 and AVS20 of the small normal lung volume group were all significantly lower than those of the large normal lung volume group (p<0.001). CONCLUSION: The effects of tumor volume and normal lung volume on dose-volume parameters should be considered. AVS5 is an important supplementary dose limitation parameter for patients whose tumor volume exceeds a certain boundary value (approximately 300 cm3).